Comunicação, recepção e consumo: inter-relações. O receptor/consumidor no prime time brasileiro e português - Macedo, Diana Gualberto de (2010)
Since we live in a consumer society, we consider very important to get to know it, which means, to understand better the process of consumption. We try to get to know the receptors/consumers in their daily cultural practices, considering the consumption of the media and the consumption of material/symbolical goods, through the inter-relations communication, reception and consumption. The object of this research are the relations between communication/reception/consumption in three categories of television time slot: news, soap opera and advertising, inserted in the brazilian and portuguese prime time, especially advertising, due to its close relationship with both sides: production and consumption. This research attempts to identify the profile of receptors/consumers “draw” in each of these categories, which means, to understand with whom they dialogue in particular and, secondly, to investigate with the receptors/consumers the appropriations and attribution of meanings to the media categories already established, through the application of questionnaires with open and closed questions and focus group.